Intestinal gluconeogenesis prevents obesity-linked liver steatosis and non-alcoholic fatty liver disease. Issue 12 (23rd March 2020) - Vily-Petit, Justine; Soty-Roca, Maud; Silva, Marine; Raffin, Margaux; Gautier-Stein, Amandine; Rajas, Fabienne; Mithieux, Gilles
Abstract : Objective: Hepatic steatosis accompanying obesity is a major health concern, since it may initiate non-alcoholic fatty liver disease (NAFLD) and associated complications like cirrhosis or cancer. Intestinal gluconeogenesis (IGN) is a recently described function that contributes to the metabolic benefits of specific macronutrients as protein or soluble fibre, via the initiation of a gut-brain nervous signal triggering brain-dependent regulations of peripheral metabolism. Here, we investigate the effects of IGN on liver metabolism, independently of its induction by the aforementioned macronutrients. Design: To study the specific effects of IGN on hepatic metabolism, we used two transgenic mouse lines: one is knocked down for and the other overexpresses glucose-6-phosphatase, the key enzyme of endogenous glucose production, specifically in the intestine. Results: We report that mice with a genetic overexpression of IGN are notably protected from the development of hepatic steatosis and the initiation of NAFLD on a hypercaloric diet. The protection relates to a diminution of de novo lipogenesis and lipid import, associated with benefits at the level of inflammation and fibrosis and linked to autonomous nervous system. Conversely, mice with genetic suppression of IGN spontaneously exhibit increased hepatic triglyceride storage associated with activated lipogenesis pathway, in the context of standard starch-enriched diet. The latter is corrected by portal glucose infusion mimicking IGN. Conclusion: We conclude that IGN per se has the capacity of preventing hepatic steatosis and its eventual evolution toward NAFLD.